The Influence of Financial Literacy and Lifestyle Against Consumptive Behavior of Generation Z during the Covid-19 Pandemic - Ratri Paramitalaksmi; Wuku Astuti; Hadjija Dewi Aviva (Ilomata International Journal of Social Science, 2022)
This study aims to determine the influence of financial literacy and lifestyle levels against consumptive behavior of Generation Z during the Covid-19 pandemic in Special Region of Yogyakarta, Indonesia. The method used in this study was by distributing questionnaires to 200 students in D.I. Yogyakarta Province by sampling method through Google Form. This sampling determination is expected to be a representative of Generation Z i in Special Region of Yogyakarta, Indonesia. The result of this study is that lower level of Financial Literacy, the higher the consumptive behavior of Generation Z in Special Region of Yogyakarta, Indonesia during the Covid-19 pandemic. On the other hand, the higher the Lifestyle, the higher the Consumptive Behavior of Generation Z in Special Region of Yogyakarta, Indonesia during the Covid-19 Pandemic.